#### Answer

$-12$

#### Work Step by Step

$3x(y+z)$ $\longrightarrow$ substitute
=$3(2)(-5+3)$ $\longrightarrow$ solve expression in parenthesis
=$3(2)(-2)$$\longrightarrow$ multiply
=$6(-2)$
=$-12$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

$-12$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.